A review of Breast Cancer risk factor assessment on women in developing countries, cancer drug resistance, and Breast Cancer treatment in Bangladesh - Raihan, Dilraj (Brac University, 2024)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2023.